Rapid screening analysis of antioxidant activities in green tea products using DPPH and FRAP - Setiawan, Vendra; Phangestu, Sherlly; Soetikno, Agatha Grace; Arianti, Angelina; Kohar, Indrajati (Brawijaya University, 2021)
Free radicals are formed inside and outside the body. Free radicals inside the body can be created in the cell compartments. The reactions are complex through the initiation, propagation, and termination stages. On the other hand, free radicals in the outer body can be formed from pollutions and environmental damage action.Â Excessive free radicals cause oxidative stress and use destructive cellular to affect health conditions. Antioxidants are known as essential agents in biological systems against diseases triggered by free radicals. One of the many antioxidants found in tea plants (Camellia sinensis) is polyphenols. A colorimetry method was employed to evaluate the dominant antioxidant compound of the total phenolic and flavonoid content in two selected tea products. The total phenolic content was determined by utilizing the Folin-Ciocalteu reagent. In addition, an aluminum colorimetric assay is applied to assess flavonoid content. Rapid screening of antioxidant activity using a spectrophotometric method is employed to determine IC50 values of tea extracts utilizing DPPH and FRAP. The FRAP method showed more sensitivity in determining antioxidant activities with the feasibility of working in low analyte concentrations than the DPPH method. The high total phenolic and flavonoid contents found in this experiment are in line with low IC50 values. It was also found out that brewed green tea has lower total phenol content than green tea bags.